Innovations in Vascular Repair from Mechanical Intervention to Regenerative Therapies - Park, Hye Min; Kim, Chae Lin; Kong, Dasom; Heo, Seon Hee; Park, Hyun Ji (Tissue Engineering and Regenerative Medicine, 2025)
Background: Vascular diseases, including atherosclerosis and thrombosis, are leading causes of morbidity and mortality worldwide, often resulting in vessel stenosis that impairs blood flow and leads to severe clinical outcomes. Traditional mechanical interventions, such as balloon angioplasty and bare-metal stents, provided initial solutions but were limited by restenosis and thrombosis. The advent of drug-eluting stents improved short-term outcomes by inhibiting vascular smooth muscle cell proliferation, however, they faced challenges including delayed reendothelialization and late-stage thrombosis. Methods: This review highlights the progression from mechanical to biological interventions in treating vascular stenosis and underscores the need for integrated approaches that combine mechanical precision with regenerative therapies. Results: To address long-term complications, bioresorbable stents were developed to provide temporary scaffolding that gradually dissolves, yet they still encounter challenges with mechanical integrity and optimal degradation rates. Consequently, emerging therapies now focus on biological approaches, such as gene therapy, extracellular vesicle treatments, and cell therapies, that aim to promote vascular repair at the cellular level. These strategies offer the potential for true vascular regeneration by enhancing endothelialization, modulating immune responses, and stimulating angiogenesis. Conclusion: Integrating mechanical precision with regenerative biological therapies offers a promising future for treating vascular stenosis. A comprehensive approach combining these modalities could achieve sustainable vascular health.
Keywords: Blood flow; Blood lead; Mechanical; Mechanical precision; Regenerative therapy; Stenoses; Stent technology; Vascular disease; Vascular repair; Vascular stenosis; Animals; Humans; Regeneration; Regenerative Medicine; Vascular Diseases; Regenerative therapies; Stent technologies; Vascular repair